O licenciamento ambiental: contribuições para um marco legislativo à luz do pacto federativo ecológico instituído pela Lei Complementar 140/2011 - Milaré, Lucas Tamer (2016)
In Brazil, the environmental licensing process entered, in an innovative way, the gates of the environmental control agencies in the states of Rio de Janeiro (1975 ) and São Paulo (1976 ) and, only since 1981, with the enactment of the National Environmental Policy though Law 6,938/1981 and the creation of the National Environmental System - SISNAMA, has developed a national coverage. It is through this instrument that the Public Power, when examining the submitted projects, check their suitability to the principles of National Environmental Policy, assess the positive and negative consequences of their implementation, in terms of environmental aspects, in the view of the sustainable development, and decides by the authorization of their implementation, formulating the necessary requirements to minimize their negative environmental impacts and to maximize its positive impacts. Throughout its application, however, there have been dissatisfactions of all types. The main complaints relate to the excess of rules related to the matter, many outdated and inaccurate, the high costs, delays and excessive bureaucracy to obtain environmental licenses. For this reason, there should be no delay in the adoption of measures necessary for its improvement, because, as it is well known, there are many opportunities at the moment related to the growth of our economy, but there are also many obstacles that need to be overcome for the achievement of this goal. Among them is the need for more stable regulatory and institutional environments, providing greater legal certainty and less bureaucracy, favorable to the performance of the productive sector and the growing demand for investment in all productive sectors. Indeed, in a globalized world, Brazil, to be able to compete, must reduce its production costs and develop its capacity to technological innovation, in addition to overcome structural bottlenecks, such the ones related to the infrastructure area, which will be possible solely with the efficiency of the licensing process, which, unfortunately, in the the view of many, is nothing but a stubborn obstacle to development. Within this context, our commitment, far from any pretense, focused - based on indicators of qualified sources: World Bank, Secretariat of Strategic Affairs of the Presidency, the National Industry Confederation, the Brazilian Association of State Entities Environment and Legislative Advisory Chamber of Deputies – in the identification of the main structural problems of environmental licensing process in Brazil, with the objective to present, de lege ferenda, contributions to its improvement. Thus, in the course of our investigations, surrounded with a myriad of innovative legislative proposals already under way in Congress, we seek not just point the fragmentation and non-systemicity of existing rules, but mainly the opportunity to approve a legal instrument that will the discipline, in the light of new ecological federal pact established by Complementary Law 140/2011, the general rules for environmental licensing, capable, in short term, to guide an uniform environmental management system for the entire country